“Being a dancer is not only a passion” – dance forms in the prose works of Milan Kundera - Cieliczko, Małgorzata (Bohemistyka, 2018)
The author of this article analyses the way in which dance and the dancer function within the prose works of Milan Kundera. Preceded by an introduction which analyses the figure of homo saltans from a cultural perspective, this review of the topic of dance (understood phenomenologically) presents four literary aspects in which it reveals itself. These perspectives are not conflicting, but neither are they complementary. The first relates to ritual rites of dancing in a circle, and their (crooked) reflection can be seen in the socio-political experience of the 20th century. The second presents dance as a narrative element, which asks questions about its own nature, and therefore has an autotelic and universalising character. The third aspect presents a metaphorical understanding of dance movement, while the fourth relates to philosophies of the dance and the dancer, as proposed by one of the protagonists in Slowness, leading this persona away from aesthetics towards the experience of public life. According to the author of this article, dance is used by Kundera to discover more interesting layers of the human condition, but much here depends on the reader.